Inventare una lingua segreta in classe: consapevolezza metalinguistica e apprendimento L2 - Gobbo, Federico (Incontri. Rivista europea di studi italiani, 2018)
The invention of a secret language in the classroom Metalinguistic awareness and L2 learning Within the context of the Montessori School of Milan (Italy, via Milazzo) there is an innovative language laboratory held over two school years (pupils’ age: 9-11). The main goal of this laboratory is to foster pupil’s metalinguistic awareness, through the collective invention of a secret language belonging to all class members, with the help of researchers and teachers. Usually, languages are invented for artistic purposes − such as Star Trek Klingon − or for international communication, as was the case with Esperanto. It is less common to invent languages for didactic purposes. In this laboratory, every class invents its own secret language starting from the phonetic space until idioms and translation, passing through morphology and syntax. A lot of attention is paid to the language of instruction, i.e. Italian, by contrast: the invented language should be different enough from Italian in order to guarantee secrecy. The presence of many pupils belonging to families speaking at home languages different from Italian shows how the process of invention permits them to dramatically improve their competence in Italian being an L2 in a fun way, especially by writing bilingual texts Italian-secret language.